2022
DOI: 10.1155/2022/1296816
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PINK1-AS Aggravates Cerebral Ischemia/Reperfusion Oxidative Stress Injury through Regulating ATF2 by Sponging miR-203

Abstract: Ischemic stroke is a common disease that led to high mortality and high disability. NADPH oxidase 2- (NOX2-) mediated oxidative stress and long noncoding RNA have important roles in cerebral ischemia/reperfusion (CI/R) injury, whereas whether there is interplay between them remains to be clarified. This study was performed to observe the role of lncRNA PINK1-antisense RNA (PINK1-AS) in NOX2 expression regulation. An in vivo rat model (MCAO) and an in vitro cell model (H/R: hypoxia/reoxygenation) were utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…PINK1-AS knockdown increases ROS levels in glioma cells, promotes mitochondrial ssion, and decreases aerobic glucose metabolism levels in glioma. However, one study reported a positive correlation between PINK1-AS expression level and ROS production level [17]. This may be affected by differences in cell lines or stages of disease development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PINK1-AS knockdown increases ROS levels in glioma cells, promotes mitochondrial ssion, and decreases aerobic glucose metabolism levels in glioma. However, one study reported a positive correlation between PINK1-AS expression level and ROS production level [17]. This may be affected by differences in cell lines or stages of disease development.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, PINK1-AS is closely associated with PD development and occurrence. Additionally, PINK1-AS is associated with gastric cancer tumorigenesis and cerebral ischemia/reperfusion oxidative stress injury [16,17]; however, its role in glioma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells, for example, a correlation between Mir7 and Pink1 seems to exist [55]. A causal relationship between the Mir203 and Pink1 was also shown for neurons [55,56]. To what extent these are cell line-specific effects and whether these mechanisms are relevant to tumor cells must currently remain open.…”
Section: Genes Related To Tumor Progressionmentioning
confidence: 99%
“…It has been found that NADPH oxidase 2 (NOX2) plays a key role in CI/R-induced oxidative stress injury and is a key enzyme causing ROS [ 63 ]. In addition, several studies showed that decreasing NOX2 expression and reducing NOX activity are two effective ways to attenuate CIRI [ 64 ]. When studying the protective mechanism of ischemic preconditioning, some researchers found that ischemic preconditioning (IPC) can induce cerebral ischemic tolerance, which is initiated by oxidative stress.…”
Section: Oxidative Stress and Cerebral Ischemic Strokementioning
confidence: 99%